CO2 coverage on Pd catalysts accelerates oxygen removal in oxy-combustion systems. Issue 8 (14th February 2023) - Jung, Sungyoon; Cao, Tengfei; Mishra, Rohan; Biswas, Pratim
Abstract : Accelerated CO2 generation was observed during complete CH4 oxidation with increased CO2 concentration in the feed stream. Abstract : Oxy-combustion systems result in enriched CO2 in exhaust gases; however, the utilization of the concentrated CO2 stream from oxy-combustion is limited by remnant O2 . CH4 oxidation using Pd catalysts has been found to have high O2 -removal efficiency. Here, the effect of excess CO2 in the feed stream on O2 removal with CH4 oxidation is investigated by combining experimental and theoretical approaches. Experimental results reveal complete CH4 oxidation without any side-products, and a monotonic increase in the rate of CO2 generation with an increase in CO2 concentration in the feed stream. Density-functional theory calculations show that high surface coverage of CO2 on Pd leads to a reduction in the activation energy for the initial dissociation of CH4 into CH3 and H, and also the subsequent oxidation reactions. A CO2 -rich environment in oxy-combustion systems is therefore beneficial for the reduction of oxygen in exhaust gases.